A hitchhiker's guide to European lake ecological assessment and intercalibration. (May 2015) - Poikane, Sandra; Birk, Sebastian; Böhmer, Jürgen; Carvalho, Laurence; de Hoyos, Caridad; Gassner, Hubert; Hellsten, Seppo; Kelly, Martyn; Lyche Solheim, Anne; Olin, Mikko; Pall, Karin; Phillips, Geoff; et al.
Highlights: Over 90 lake ecological assessment methods are currently in use across Europe. To ensure methods comparability, intercalibration was carried out by Member States. 62 lake assessment methods were intercalibrated and published in an EC Decision. We present an overview of the lake assessment methods and their intercalibration. Furthermore, the gaps of lake assessment in Europe and way forward are discussed. Abstract: The Water Framework Directive is the first international legislation to require European countries to establish comparable ecological assessment schemes for their freshwaters. A key element in harmonising quality classification within and between Europe's river basins is an "Intercalibration" exercise, stipulated by the WFD, to ensure that the good status boundaries in all of the biological assessment methods correspond to similar levels of anthropogenic pressure. In this article, we provide a comprehensive overview of this international comparison, focusing on the assessment schemes developed for freshwater lakes. Out of 82 lake ecological assessment methods reported for the comparison, 62 were successfully intercalibrated and included in the EC Decision on intercalibration, with a high proportion of phytoplankton (18), macrophyte (17) and benthic fauna (13) assessment methods. All the lake assessment methods are reviewed in this article, including the results of intercalibration. Furthermore, the current gaps and way forward to reach consistent management objectives for European lakes are discussed.